Enhancing problem-solving skills of novice programmers in an introductory programming course - Malik S.I.; Mathew R.; Al-Sideiri A.; Jabbar J.; Al-Nuaimi R.; Tawafak R.M. (John Wiley and Sons Inc, 2023)
Internet protocols; Learning algorithms; Learning systems; Semantics; Teaching; Introductory programming; Introductory programming course; Problem solving skills; Programming exercise; Programming knowledge; Semi structured interviews; Students' behaviors; Traditional approaches; Students